Towards a long-term tephrochronological framework for synchronisation of archaeological records in the Armenian Highlands and southern caucasus for MIS3: new data from Ararat-1 and Kalavan-2 sites - S.P.E. Blockley; R.G.O. Timms; K. Flowers; A. Carter-Champion; I. Oikonomou; T. Karampaglidis; R.J. Kearney; H. Hawkins; J.E. Sherriff; B. Gasparyan; A. Petrosyan; A. Malinsky-Buller (Quaternary Science Reviews, 2026)

Edible Campus: Empowering Students Through Integrated Campus Gardening and Meal Preparation Programs - J. Lefaver; C. Starr; D. Folliard; B. Flower; J. Patterson; M. Duffrin (Journal of the Academy of Nutrition and Dietetics, 2025)

Effect of biosecurity practices and diseases on growth and carrageenan properties of Kappaphycus alvarezii and Eucheuma denticulatum cultivated in Zanzibar, Tanzania - Msafiri A. Ndawala; Flower E. Msuya; Jennefe P. Cabarubias; Cicilia S. B. Kambey; Amelia S. Buriyo; Esther F. Mvungi; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2022)

Biosecurity policy and legislation of the seaweed aquaculture industry in Tanzania - Sadock B. Rusekwa; Iona Campbell; Flower E. Msuya; Amelia S. Buriyo; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Pest and disease outbreaks have significant impacts on the livelihoods of seaweed farmers each year, particularly in low- to middle-income countries around the world. Commercial seaweed farming of the red carrageenophytes, Eucheuma denticulatum , Kappaphycus alvarezii and Kappaphycus striatus , in Tanzania was established in 1989. The impacts of pests and diseases on the local seaweed industry had serious implications for the environment, society, local culture and human health. The industry was initially characterised by growth, but since 2002 has been severely limited due to pest and disease outbreaks, exacerbated by the effects of climate change. This paper identifies existing biosecurity frameworks in Tanzanian legislation and policies in order to assess their content regarding the management of pests and diseases in the seaweed industry. A total of thirteen frameworks were identified and analysed for their general biosecurity scope and inclusion of specific risks. Of the thirteen, only four were legally binding, and only four were identified to be applicable to the seaweed industry. National frameworks were predominantly designed to support finfish aquaculture; therefore, national authorities lack the expertise, experience and scientific basis on biosecurity issues in seaweed industry compared with other aquatic commercial commodities to identify and mitigate the risks from pest and disease outbreaks in the seaweed farming industry. Recommendations are provided to assist regulators in establishing biosecurity policies, which either explicitly include or are specifically designed, to support the Tanzanian seaweed industry. This analysis reveals where biosecurity capacity can be developed to support a sustainable and economically productive national seaweed farming industry.

Biosecurity policy and legislation for the global seaweed aquaculture industry - Iona Campbell; Cicilia S. B. Kambey; Jonalyn P. Mateo; Sadock B. Rusekwa; Anicia Q. Hurtado; Flower E. Msuya; Grant D. Stentiford; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Each year a significant proportion of global food production is lost to pests and diseases, with concerted efforts by government and industry focussed on application of effective biosecurity policies which attempt to minimise their emergence and spread. In aquaculture the volume of seaweeds produced is second only to farmed fish and red algal carrageenophytes currently represent approximately 42% of global production of all seaweeds. Despite this importance, expansion of the seaweed sector is increasingly limited by the high prevalence of recalcitrant diseases and epiphytic pests with potential to emerge and with the demonstrated propensity to spread, particularly in the absence of effective national and international biosecurity policies. Developing biosecurity policy and legislation to manage biosecurity risk in seaweed aquaculture is urgently required to limit these impacts. To understand current international biosecurity frameworks and their efficacy, existing legislative frameworks were analysed quantitatively for the content of biosecurity measures, applicability to the seaweed industry, and inclusion of risks posed by diseases, pests and non-native species. Deficiencies in existing frameworks included the following: inconsistent terminology for inclusion of cultivated seaweeds, unclear designation of implementation responsibility, insufficient evidence-based information and limited alignment of biosecurity hazards and risks. Given the global importance of the cultivation of various seaweeds in alleviating poverty in low and middle income countries, it is crucial that the relatively low-unit value of the industry (i.e. as compared with other aquatic animal sectors) should not conflate with a perceived low risk of disease or pest transfer, nor the subsequent economic and environmental impact that disease transfer may impact on receiving nations (well beyond their seaweed operations). Developing a clear basis for development of robust international biosecurity policies related to the trade in seaweeds arising from the global aquaculture industry, by first addressing the gaps highlighted in this study, will be crucial in limiting impacts of pests and diseases on this valuable industry and on natural capital in locations where seaweeds are farmed.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

First detection of gas bubble disease and Rickettsia ‐like organisms in Paphies ventricosa , a New Zealand surf clam - P M Ross; A Pande; J B Jones; J Cope; G Flowers (Journal of Fish Diseases, 2018)

Diatom taphonomy and silica cycling in two freshwater lakes and their implications for inferring past lake productivity - David B. Ryves; N. John Anderson; Roger J. Flower; Brian Rippey (Journal of Paleolimnology, 2013)

Effect of low salinity on ion accumulation, gas exchange and postharvest drought resistance and habit of Coriandrum sativum L. - Uliana B. Bashtanova; Timothy J. Flowers (Plant and Soil, 2012)

Inbreeding and inbreeding depression of early life traits in a cooperative mammal - JOHANNA F. NIELSEN; SINEAD ENGLISH; WILL P. GOODALL‐COPESTAKE; JINLIANG WANG; CRAIG A. WALLING; ANDREW W. BATEMAN; TOM P. FLOWER; ROBERT L. SUTCLIFFE; JAMIE SAMSON; NATHAN K. THAVARAJAH; LOESKE E. B. KRUUK; TIM H. CLUTTON‐BROCK; et al. (Molecular Ecology, 2012)
Mating between relatives often results in negative fitness consequences or inbreeding depression. However, the expression of inbreeding in populations of wild cooperative mammals and the effects of environmental, maternal and social factors on inbreeding depression in these systems are currently not well understood. This study uses pedigree‐based inbreeding coefficients from a long‐term study of meerkats ( Suricata suricatta ) in South Africa to reveal that 44% of the population have detectably non‐zero ( F > 0) inbreeding coefficients. 15% of these inbred individuals were the result of moderate inbreeding ( F ≥ 0.125), although such inbreeding events almost solely occurred when mating individuals had no prior experience of each other. Inbreeding depression was evident for a range of traits: pup mass at emergence from the natal burrow, hind‐foot length, growth until independence and juvenile survival. However, we found no evidence of significant inbreeding depression for skull and forearm length or for pup survival. This research provides a rare investigation into inbreeding in a cooperative mammal, revealing high levels of inbreeding, considerable negative consequences and complex interactions with the social environment.

Diversity and physiological plasticity of vegetable genotypes of coriander improves herb yield, habit and harvesting window in any season - Uliana B. Bashtanova; Timothy J. Flowers (Euphytica, 2011)

Application of remote sensing to site characterisation and environmental change analysis of North African coastal lagoons - M. H. Ahmed; B. M. El Leithy; J. R. Thompson; R. J. Flower; M. Ramdani; F. Ayache; S. M. Hassan (Hydrobiologia, 2009)

Altered temporal profile of visual–auditory multisensory interactions in dyslexia - W. David Hairston; Jonathan H. Burdette; D. Lynn Flowers; Frank B. Wood; Mark T. Wallace (Experimental Brain Research, 2005)

Quantitative and qualitative relationships between planktonic diatom communities and diatom assemblages in sedimenting material and surface sediments in Lake Baikal, Siberia - David B. Ryves; David H. Jewson; Michael Sturm; Richard W. Battarbee; Roger J. Flower; Anson W. Mackay; Nikolai G. Granin (Limnology and Oceanography, 2003)
Endemic planktonic diatoms are a major component of Lake Baikal sediments during interglacial periods. To investigate how these diatom assemblages are altered during sediment formation, quantitative plankton monitoring (1995–1998) was integrated with sediment trapping over 2 yr (1996–1997) in Baikal's southern basin (depth ~1,400 m). The traps consisted of both open (~6 monthly) and sequential (~2 weekly) collectors deployed throughout the water column. Sedimentation was seasonal, with diatom species composition, valve abundance, and total dry massreflecting changes in the planktonic communities. Sedimented assemblages were transmitted largely intact to the deepest traps (~1,300–1,390 m); some compositional blurring occurred from differential sinking rates and dissolution of diatom valves. A rapid mass flux event of Aulacoseira skvortzowii and A. baicalensis was recorded in summer 1997 with particle sinking rates between 60 and 100 m d −1 and dry mass fluxes >5 g m −2 d −1 . Although dissolution was evident for all species, more delicate taxa were preferentially affected (e.g., A. skvortzowii vegetative cells and fine Synedra species), whereas Nitzschia acicularis valves were almost entirely dissolved within the water column. Comparing trap and plankton diatom assemblages with those in nearby core tops demonstrated that a fundamental taphonomic change occurs in the surface sediment, with sedimentary diatom accumulation rates being only about 1% of trap deposition and plankton production rates. Dissolution was significant in explaining 5–30%

Assessing the potential for developing internal diatom‐based transfer functions for Lake Baikal - Anson W. Mackay; Richard W. Battarbee; Roger J. Flower; Nicholas G. Granin; David H. Jewson; David B. Ryves; Michael Sturm (Limnology and Oceanography, 2003)
We explore possible quantitative relationships between diatom species and environmental data for Lake Baikal using multivariate techniques. Our approach differs from published studies in other regions (on training sets and transfer functions) because (1) although only one lake is examined, we use the internal lake gradients rather than gradients among lakes and (2) the majority of the dominant diatom taxa are endemic. Canonical correspondence analysis on 93 surface sediment diatom assemblages reveals that major taxa show distinct relationships with measured environmental variables. Five significant variables were identified: snow thickness on ice (which accumulates on the frozen lake surface between January and April/May), water depth, suspended matter, annual solar radiation, and mean July temperature of surface waters. The strongest relationship is with snow thickness, which influences light levels in the water below the ice. A diatom‐based inference model has been developed to predict snow thickness on the ice using weighted averaging (WA) and WA with tolerance down‐weighting (WA tol ) models. Results suggest that Lake Baikal diatom assemblages in surface sediments can be used to develop a robust model for estimating snow thickness across frozen Lake Baikal (r 2 jack = 0.607, RMSEP = 0.138 log cm). This model has potential applications for recent paleoclimate studies in this region of continental Eurasia.

Terrestrial pollen record of recent land-use changes around nine North African lakes in the CASSARINA Project - Sylvia M. Peglar; Hilary H. Birks; H. J. B. Birks; A.A. Fathi; R.J. Flower; M.M. Kraïem; S.T. Patrick; M. Ramdani (Aquatic Ecology, 2001)

Surface-sediment and epilithic diatom pH calibration sets for remote European mountain lakes (AL:PE Project) and their comparison with the Surface Waters Acidification Programme (SWAP) calibration set - N. G. Cameron; H. J. B. Birks; V. J. Jones; F. Berges; J. Catalan; R. J. Flower; J. Garcia; B. Kawecka; K. A. Koinig; A. Marchetto; P. Sánchez-Castillo; R. Schmidt; et al. (Journal of Paleolimnology, 1999)